What caused ozone pollution during the 2022 Shanghai lockdown? Insights from ground and satellite observations - Y. Tan; T. Wang (Atmospheric Chemistry and Physics, 2022)
Shanghai, one of China's most important economic centres, imposed a citywide lockdown in April and May 2022 to contain a resurgence in cases of the coronavirus disease in 2019. Compared with the 2020 lockdown, the 2022 lockdown occurred in a warm season and lasted much longer, thereby serving as a relevant real-world test of the response of ambient ozone (O3) concentrations to emission reductions in a high-O3 season. In this study, we analysed surface observations of O3 and nitrogen dioxide (NO2) concentrations and satellite-retrieved tropospheric NO2 and formaldehyde (HCHO) column concentrations in the first 5 months of 2022 with comparisons to the year 2021. During the 2-month 2022 lockdown, the maximum daily 8 h average (MDA8) O3 concentrations at 1 or more of the city's 19 sites exceeded China's air quality standard of 160 µg m−3 21 times, with the highest value being 200 µg m−3. The city-average MDA8 O3 concentration increased by 13 % in April–May 2022 year-on-year, despite sharp declines in NO2 surface and column concentrations (both by 49 %) and a 19 % decrease in the HCHO column concentration. These results show that the reductions in O3 precursors and other pollutants during the 2022 lockdown did not prevent ground-level O3 pollution. An analysis of meteorological data indicates that there were only small changes in the meteorological conditions, and there was little transport of O3 from the high-O3 inland regions during the 2022 lockdown, neither of which can account for the increased and high concentrations of O3 that were observed during this period. The mean HCHO/NO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="61pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="870ef42d69c70c325b36be1c93f8e2bd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-14455-2022-ie00001.svg" width="61pt" height="14pt" src="acp-22-14455-2022-ie00001.png"/></svg:svg> ratio in April–May increased from 1.11 in 2021 to 1.68 in 2022, and the correlation between surface O3 and NO2 concentrations changed from negative in 2021 to positive in 2022. These results indicate that the high O3 concentrations in 2022 were mainly due to large reductions in the emissions of NOx and that the decrease in the concentrations of volatile organic compounds (VOCs) could not overcome the NO titration effect. During the 2022 lockdown, Shanghai's urban centre remained VOC-sensitive despite drastic reductions in road transportation (73 %–85 %) and industrial activities (∼60 %), whereas its semi-rural areas transitioned from VOC-limited to VOC–NOx-co-limited regimes. Our findings suggest that future emission reductions similar to those that occurred during the lockdown, such as those that will result from electrifying transportation, will not be sufficient to eliminate O3 pollution in urban areas of Shanghai and possibly other VOC-limited metropoles without the imposition of additional VOC controls or more substantial decreases in NOx emissions.